Pengaruh Green Marketing dan Corporate Social Responsibility terhadap Brand Image dan Purchase Intention Serta Purchase Decision (Studi pada The Body Shop di Samarinda) - Hudyah Astuti Sudirman; Theresia Militina; Dodhy Adhimursandi (Jurnal Ilmu Manajemen Mulawarman (JIMM), 2020)
This study aims to analyze and determine the influence of green marketing and corporate social responsibility on brand image, purchase intention, and purchase decision on The Body Shop’s customers in Samarinda. This study uses a quantitative approach using SmartPLS software. The sample were 152 respondents with a sampling technique using accidental sampling. The results showed that green marketing is significantly positive effect on the brand image. Green marketing is significantly positive effect on purchase intention. Corporate social responsibility is not significantly positive effect on brand image. Corporate social responsibility is significantly positive effect on purchase intention. Green marketing is significantly positive effect on the purchase decision. Corporate social responsibility is not significantly positive effect on the purchase decision. Brand image is significantly positive effect on the purchase decision. Purchase intention is significantly positive effect on the purchase decision.